Households response to economic crisis - Petr Jakubik (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This paper studies the economic impact of the current global economic downturn on the household sector. Household budgets can be negatively affected by declines in nominal wages and increases in unemployment. We empirically test this effect for the small open emerging economy. As a result of a lack of individual data on household finances, micro data are simulated. Our analysis clearly shows that there is a significant additional decline in consumption related to an increase in household default rates and unemployment. We find that potential household insolvencies have important implications for the financial system as well as for the macroeconomy.
URN:NBN:fi:bof-201408072067
Keywords: 330